2014
DOI: 10.1016/j.jcsr.2014.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of ring-shaped steel plate shear walls

Abstract: A new type of steel plate shear wall has been devised which resists out--of--plane buckling without requiring stiffeners. The ring--shaped steel plate shear wall (RS--SPSW) includes a web plate that is cut with a pattern of holes leaving ring--shaped portions of steel connected by diagonal links. The ring shape resists out--of--plane buckling through the mechanics of how a circular ring deforms into an ellipse. It has been shown that the ring's compression diagonal will shorten a similar amount as the tension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(19 citation statements)
references
References 4 publications
0
19
0
Order By: Relevance
“…The Ring Shaped -Steel Plate Shear Wall (RS-SPSW) is a novel structural system that can bring an industrial or modern feel to a building while also improving upon conventional SPSW performance [14]. The RS-SPSW system can act as both the lateral load resisting system and as an architectural element.…”
Section: Steel Plate Shear Wall Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ring Shaped -Steel Plate Shear Wall (RS-SPSW) is a novel structural system that can bring an industrial or modern feel to a building while also improving upon conventional SPSW performance [14]. The RS-SPSW system can act as both the lateral load resisting system and as an architectural element.…”
Section: Steel Plate Shear Wall Backgroundmentioning
confidence: 99%
“…This eliminates slack, or buildup of material, in the transverse (compression) direction. Slack material along the compression diagonal is one way to think about the cause of shear buckling and it has been shown that the ring shape is capable of preventing this shear buckling [14]. For a solid plate subjected to a tension elongation, δ 1 (Figure 7b), the transverse shortening, δ 2 is approximately equal to δ 1 multiplied by the Poisson's ratio, which is 0.3 for steel.…”
Section: Conceptsmentioning
confidence: 99%
“…In [23], on the basis of the experimental tests carried out by Egorova et al [24], a numerical model on a steel plate with a pattern of holes leaving ring-shaped portions of steel connected by diagonal links was developed. The dissipative capacity of the system was guaranteed by the plastic mechanism activated when steel circular rings deformed into ellipses; moreover the presence of the diagonal links allowed the mitigation of possible out-of-plane buckling.…”
Section: Numerical Analysesmentioning
confidence: 99%
“…Weakening of the infill plate have also been tried by creating a regular pattern of circular perforations (Roberts and Sabouri-Ghomi, 1992;Vian et al, 2009), or by using low yield point (LYP) steel plates (Vian et al, 2003). Researchers have also tried to change the load carrying mechanism in the infill plate by providing slits (Hitaka and Matsui, 2003;Cortés and Liu, 2011) or by cutting out special patterns on the wall (Egorova et al, 2014). Application of these passive methods has resulted in reducing the lateral forces acting on the columns but not eliminating them, and often requiring additional material and labour costs, and increased construction time.…”
Section: Background and The Past Researchmentioning
confidence: 99%